-4-4p=24

Simple and best practice solution for -4-4p=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-4p=24 equation:


Simplifying
-4 + -4p = 24

Solving
-4 + -4p = 24

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -4p = 24 + 4

Combine like terms: -4 + 4 = 0
0 + -4p = 24 + 4
-4p = 24 + 4

Combine like terms: 24 + 4 = 28
-4p = 28

Divide each side by '-4'.
p = -7

Simplifying
p = -7

See similar equations:

| 3x+1-1=3x+2 | | 20x(4-2)= | | 4(7v-8)=136 | | 8X+12Y=(X+Y) | | 2(y-5)=7y+8 | | 3y-2x=m | | N^2-81n=0 | | -9p-4=50 | | -8(n-1)=5-8n | | -9p-4=40 | | =9E-07(551.368) | | 49=413c-7 | | 10(3x-5)=100x | | -5(4y-2)-y=-4(y-2) | | 6n+3n+3120=5400 | | -6+-1y=10 | | -7p-4=2p+40 | | 17=102 | | 6+-1y=10 | | 2(3s+2)=76 | | -4.9m^2+34.3m+0=58.8 | | 10(2x-11)=90x | | 2x+Y+4z=19 | | 12=15-9(3) | | 4x+2x-x= | | 13+(29+7)=13+(7+29) | | -5(x+3)=-14-4x | | R=4x+12 | | 3-(3x-6)=2+5x | | C(m)=0.5m+25 | | 5(2l+7)=55 | | 6z^2+7z+2=0 |

Equations solver categories